ANALISIS SWOT TERHADAP RENCANA STRATEGIS IT PERUSAHAAN - mardiana - - (Jurnal Eksplora Informatika, 2018)
PT. Indah Logistik Cargo has been using information technology in every work process. IT strategic plan is necessary to improve the quality and service quality so as not to be abandoned by its customers. The purpose of this study was the identification of the company's condition to the IT strategic plan with Ã‚ SWOT analysis. By utilizing information technology to expedite the service process, increase efficiency, and avoid the costs of information technology over budget. The research used descriptive methods. Consisting of 30 respondents who are employees of PT. Indah Logistik Cargo and 30 questions with 4 variables. SPSS 15.0 was used to test the validity of each indicator question. By translating the vision and mission into strategic IT plan, the researchers stressed the problems on internal and external environmental factors of the company. Matrix IFAS and EFAS performed to determine which variables are included in the strength, weakness, opportunities, threats. From the results obtained value of the weighting matrix of x and y, where x = 0.01 and y = 0.15. The value indicates that quadrant of the SWOT matrix is Ã¢â‚¬â€¹Ã¢â‚¬â€¹at a positive value, this position explains the company is in a strong condition and opportunity.